MARKETING INNOVATION IN THE DIGITAL ERA : INCREASING CAPITAL AT STIKOM CKI THROUGH TECHNOLOGY AND SOCIAL MEDIA - Muhammad Farrel Ardan (CV. Radja Publika, 2025)
Marketing innovation in the digital era plays a crucial role in enhancing institutional capital, particularly for higher education institutions like STIKOM CKI. The rapid development of digital technologies and the increasing dominance of social media have transformed traditional marketing approaches, making digital engagement essential for institutions to remain competitive and relevant. This research explores how STIKOM CKI can leverage digital marketing strategies to improve brand visibility, increase student enrollment, and strengthen institutional capital. The study identifies key challenges faced by STIKOM CKI, including limited brand awareness, underutilization of digital tools, and ineffective stakeholder engagement strategies. To address these issues, the research proposes adopting advanced digital tools such as social media analytics, search engine optimization (SEO), and customer relationship management (CRM) systems. The findings highlight the effectiveness of platforms like Instagram, Facebook, and LinkedIn in reaching prospective students and other stakeholders. Additionally, the research emphasizes the importance of staying ahead of emerging digital trends, including artificial intelligence (AI), machine learning, and automated marketing solutions. Implementing AI-driven chatbots, personalized email campaigns, and predictive analytics can significantly enhance marketing effectiveness. In conclusion, a well-planned, data-driven digital marketing strategy will enable STIKOM CKI to attract and retain students, build stronger industry partnerships, and ensure sustainable institutional growth. By continuously adapting to the evolving digital landscape, the institution can secure its long-term success and maintain a competitive edge in the education sector.